Development of a psychological management intervention protocol for Elderly Patients with Chronic Diseases based on the Empowerment Theory: A Delphi study - Wenting Su; Hongju Yang; Chengyan Fu; Hanzong Yang (PLoS ONE, 2025)
Objective This study aims to establish a psychological intervention program for elderly patients with chronic diseases based on the theory of empowerment. Methods Through literature review, current situation surveys, and group discussions, we drafted the initial version of a psychological intervention program based on the empowerment theory. The final version of the program was developed through two rounds of Delphi expert consultations via letters. Results The response rates for two rounds both were 100% (n = 19), with an authority coefficient of 0.87. The coefficients of variation ranged from 0.05 to 0.24, and the Kendall’s W coefficient was 0.123 (P < 0.001). Ultimately, an index system comprising 7 primary items, 25 secondary items, and 98 tertiary items was established. Conclusion The psychological intervention program for elderly patients with chronic diseases based on empowerment theory is scientifically sound, specific and practical. It can provide valuable references for the psychological care of elderly patients with chronic diseases and the improvement of their self-management strategies.